Increasing the performance of diesel motors by increasing the temperature of the diesel - Taruna, Taruna; Marwiyah NST, Masringgit (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2023)
This research aims to enhance the efficiency of diesel engines by optimizing the combustion process. One of the key factors in engine efficiency is the quality of the fuel-air mixture inside the combustion chamber. Imperfect combustion leads to high fuel consumption and low engine performance. Therefore, this study employs an experimental research method to investigate the influence of preheating the diesel fuel before entering the high-pressure pump on the formation of finer fuel mist particles and a more homogenous fuel-air mixing process. A series of experiments were conducted in this research by varying the temperature of the preheated diesel fuel and measuring relevant parameters related to combustion and engine performance. The results of this study demonstrate that preheating the diesel fuel before it enters the high-pressure pump leads to an improvement in the quality of the fuel-air mixture and enhances combustion efficiency. As a consequence, there is an increase in engine power and a reduction in optimal fuel consumption. In conclusion, the use of preheated diesel fuel to enhance the combustion process can be an effective solution to optimize the performance of diesel engines and reduce fuel consumption. This research contributes significantly to finding alternatives to address the issue of high fuel consumption in diesel engine-based vehicles.